The existence of weak solutions for steady flows of electrorheological fluids with nonhomogeneous Dirichlet boundary condition. (November 2017) - Sin, Cholmin
Abstract: In this paper, we show the existence of weak solutions for steady flows of electrorheological fluids with nonhomogeneous Dirichlet boundary condition under the condition p ( x ) > 2 n n + 2, n = 2, 3 . In particular, we improve a priori estimate for weak solutions to the problem with min p ( x ) < 2, which is an improvement even for constant p .